Changes in haemodynamic parameters following Tai Chi Chuan and aerobic exercise in patients recovering from acute myocardial infarction. Issue 848 (June 1996) - Channer, K. S.; Barrow, D.; Barrow, R.; Osborne, M.; Ives, G.
Abstract : In this study, 126 patients (90 males, average age 56 years, range 39-80) were randomised to Wu Chian-Ch'uan style Tai Chi (38), aerobic exercise (41) or a non-exercise support group (47) following acute myocardial infarction. Patients attended twice weekly for three weeks then weekly for a further five weeks. Heart rate and blood pressure were recorded before and after each session. Over the 11 sessions of exercise there was a negative trend in diastolic blood pressure only in the Tai Chi group (Rs = 0.79, p < 0.01). Significant trends in systolic blood pressure occurred in both exercise groups (Rs = 0.64 and 0.63, both p < 0.05). Only four (8%) patients completed the support group eight-week programme which was less than the number completing Tai Chi (82%; p < 0.001) and aerobic exercise groups (73%; p < 0.001).